STUDENTS’ ATTITUDE TOWARDS USING WHATSAPP FOR EDUCATIONAL ACTIVITIES AT FEDERAL UNIVERSITY DUTSIN-MA, KATSINA STATE, NIGERIA - Suleiman, Ahmad, A. (FUDMA JOURNAL OF SCIENCES, 2020)
Social networking sites have been so popular among students in Nigerian universities and other parts of the world. They use them for different purposes, patterns and modes. WhatsApp is one of them. It’s a free messenger application that works across multiple platforms like iPhone and android phones. This universal application is being used widely among undergraduate students. They use it to send multimedia messages like photos, videos, audios and documents or simple text messages. It’s clear that class groups created on WhatsApp are used as medium for teaching and learning. This comes in form of communicating with students by nurturing a kind of social atmosphere in the class. It helps in framing dialogue and collaboration between the students and their teachers. This research is a descriptive survey designs. The sample size comprised of 101 undergraduate and postgraduate students who were randomly selected from the different stratified levels of clustered departments. They were derived from the seven faculties of the university. The Research developed and used questionnaire as the study’s instrument. Three (3) research questions guided this study; while the analytical tools were descriptive statistics in form of mean and standard deviation. Other tools employed were t-test and ANOVA by using SPSS version 23. Overall, findings demonstrated high level of attitude towards WhatsApp among the students. It also showed how the students use the application in various modes. The general findings confirmed that WhatsApp is being used as an academic tool for both teaching and learning in Federal University Dutsin-Ma.
Keywords: Social Media, Student Attitude, WhatsApp, Education